(3JGQjN GdLRGFQ GdKbGaj (B:s (3ef GdbQf GdYGTQ Edi GdQGHY YTQ GdgLQj (B(16-20(3e(B) (3GdLRA GdKGfj (B/s - (3CHh GdbGSe, SYO Gddgs ((3GdLRGFQ (B:s (3GdTQcI GdhWfjI ddfTQ ,s, 1981)
(3jOQS GdGfJGL GdOjfj h GdGOHj h GdJGQjNj h GdYdej NdGd GdYgO GdYKeGfjs
Keywords: (3GdYdhe GdTQYjI s; (3Yde GdcdGe s; (3GdKbGaI s; (3JGQjN GdLRGFQ s